Democratic Conundrum: Introspecting Complexities and Dynamics in Pakistan's Political Landscape - Chatterjee, Souvik (FISIP UIN Sunan Gunung Djati Bandung, 2023)
Research Problem: This research aims to explore the main obstacles hindering Pakistan's democratic transition, including weak economic policies, structural imbalances, and military interference, all of which have led to insecurity, conflict, and the oppression of civilian rule. In addition, this research also aims to understand Pakistan's political culture which combines autocratic and democratic ideologies, as well as how political satisfaction with different regimes impacts the acceptance of military regimes and the inability of marginalized groups to express their opinions under authoritarian rule. Research purposes: The aim of this research is to identify and analyze the main challenges facing Pakistan's democracy, including issues of partisanship and segregation practices, as well as to understand historical and current issues that can help identify changes needed to strengthen democracy in Pakistan. Research methods: This research uses a descriptive-analytical approach by collecting data through literature reviews and analysis of official documents, such as government reports and international agency reports. Interdisciplinary analysis is used to understand the impact of historical and socio-cultural factors on the development of democracy in Pakistan. Results and Discussion: The research results show that the main challenges to Pakistan's democracy include fraudulent electoral processes, political centralization, segregation, and biased party politics. The lack of a dynamic civil society and military domination of civilian government are contributing factors to the failure of democracy in Pakistan. Discussions of history and current issues also provide insight into the changes needed to improve democracy in the country. Research Implications and Contributions: This research has important implications for policymakers and stakeholders interested in improving democracy in Pakistan. By understanding and identifying the challenges faced, this research can provide guidance for developing appropriate strategies and measures to strengthen democracy and promote political inclusion in Pakistan.